Nurses’ perspectives on the personal and professional impact of providing nurse-led primary palliative and drug care in oncology department - Tawfiq Abdulrahman M Almadhi 7, Khalid Oudah Alahmadi 8, Abdualrhman Muqpil Alssadi9, Rami Abdullah Abotalib10, Amarat Marzoq Alblawi1, Nawal Ali Salman AL-atawi2, Bashayer awad alanzai3, Halalah rewei alatawi 4, Jamilh Defallah Nmran Alatawi5, zainab hussein mohammed alblawi6 (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Due to shortages in palliative care (PC) workforce, there is a growing need for primary PC delivered by non-specialists. The Care Management by Oncology Nurses (CONNECT) intervention equips infusion room oncology nurses with training and resources to provide primary PC. Objective: This study aims to explore nurses’ perspectives regarding the personal and professional effects of training and delivering primary PC through the CONNECT program. Methodology: The research employed qualitative methods, conducting in-depth telephone interviews with 11 nurses from oncology practices . Data analysis was carried out using qualitative content analysis. Key Findings: Nurses expressed a sense of personal and professional fulfillment in delivering primary PC through CONNECT, highlighting potential risks such as increased emotional attachment to patients. Participation in the program also enhanced nurses’ communication skills. A supportive work environment was crucial in mitigating stress associated with integrating primary PC into busy treatment schedules. Conclusion: The provision of primary PC challenges traditional task-oriented nursing practices and has the potential to reshape professional roles and workloads for infusion room nurses